Prevalence and correlates of herbal medicine use among type 2 diabetic patients in Teaching Hospital in Ethiopia: a cross-sectional study - Abebe Basazn Mekuria; Sewunet Admasu Belachew; Henok Getachew Tegegn; Dawit Simegnew Ali; Adeladlew Kassie Netere; Eskedar Lemlemu; Daniel Asfaw Erku (BMC, 2018)
Abstract Background Type 2 Diabetes Mellitus (T2DM) patients are increasingly using herbal remedies due to the fact that sticking to the therapeutic regimens is becoming awkward. However, studies towards herbal medicine use by diabetic patients is scarce in Ethiopia. Therefore, the aim of the current study was to explore the prevalence and correlates of herbal medicine use with different sociodemographic variables among type 2 diabetes patients visiting the diabetic follow-up clinic of University of Gondar comprehensive specialized hospital (UOGCSH), Ethiopia. Methods A hospital-based cross sectional study was employed on 387 T2DM patients visiting the diabetes illness follow-up care clinic of UOGCSH from October 1 to November 30, 2016. An interviewer-administered questionnaire regarding the demographic and disease characteristics as well as herbal medicine use was completed by the study subjects. Descriptive, univariate and multivariate logistic regression statistics were performed to determine prevalence and come up with correlates of herbal medicine use. Results From 387 participants, 62% were reported to be herbal medicine users. The most prevalent herbal preparations used were Garlic (Allium sativum L.) (41.7%), Giesilla (Caylusea abyssinica (fresen.) (39.6%), Tinjute (Otostegia integrifolia Benth) (27.2%), and Kosso (Hagenia abyssinicaa) (26.9%). Most of herbal medicine users (87.1%) didn't consult their physicians about their herbal medicine use. Families and friends (51.9%) were the frontline sources of information about herbal medicine followed by other DM patients who used herbal medicines (28.9%). Conclusions The present study revealed a high rate of herbal medicine use along with a very low rate use disclosure to the health care professionals. Higher educational status, a family history of DM, duration of T2DM and presence of DM complications were identified to be strong predictors of herbal medicine use. From the stand point of high prevalence and low disclosure rate, it is imperative for health care providers to strongly consult patients regarding herbal medicine use.